2017
DOI: 10.1186/s12887-017-0917-6
|View full text |Cite
|
Sign up to set email alerts
|

Transition to parenthood in the neonatal care unit: a qualitative study and conceptual model designed to illuminate parent and professional views of the impact of webcam technology

Abstract: BackgroundComplications during pregnancy, childbirth and/or the postnatal period may result in the admission of a baby to a neonatal unit (NNU). While the survival and long-term prospects of high-risk infants are enhanced by admission, the enforced separation of the parent and child may have psychological consequences for both. There is a need to develop and evaluate interventions to help parents ‘feel closer’ to their infants in circumstances where they are physically separated from them. In this paper we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 37 publications
6
66
0
Order By: Relevance
“…While the use of video is currently not common practice in neonatology, it has increased to meet new needs such as photoplethysmography, video laryngoscopy or webcams to enable virtual visit [7][8][9]. Webcams have been used [10][11][12][13][14] for several years either to limit the impact of parent-child separation or when parental presence is limited to promote early emotional bonding and reduce separation anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of video is currently not common practice in neonatology, it has increased to meet new needs such as photoplethysmography, video laryngoscopy or webcams to enable virtual visit [7][8][9]. Webcams have been used [10][11][12][13][14] for several years either to limit the impact of parent-child separation or when parental presence is limited to promote early emotional bonding and reduce separation anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals were concerned by their lack of familiarity with such a system, the risk of privacy breach, and the potential stress created due to the presence of the webcam. Kerr et al [13] found that parents and healthcare professionals consider parents' direct access to a recording of their newborn child an important improvement in neonatology.…”
Section: Introductionmentioning
confidence: 99%
“…A preterm birth also negatively influences the transition to parenthood (Rieves et al, 2016;Kerr et al, 2017), as parents, especially mothers, feel disoriented and frightened and might experience feelings of guilt, grief and recurrent worries about their baby's survival and health (Mendelsohn, 2005;Korja et al, 2009Korja et al, , 2010Shah et al, 2011;Lasiuk et al, 2013;Ionio et al, 2019;Pisoni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of parents in the NICU has increased (Al Maqhaireh et al, 2016), the environment, work routines and the complex needs of these infants become obstacles that stand in the way of a mother's role (Sisson et al, 2015;Raines & Brustad, 2013). The fragility of an extremely preterm infant can reduce the participation of parents in their care (Aydon et al, 2017;Kerr et al, 2017), and the parents' separation from the child creates stress, anxiety and a weaker bond (Kerr et al, 2017;Segre et al, 2014;Spinelli et al, 2016;Neri et al, 2017).…”
mentioning
confidence: 99%